"An important cog in the wheel", but not the driver: Coaches' perceptions of their role in doping prevention. (July 2018) - Patterson, Laurie B.; Backhouse, Susan H.
Abstract: Objectives: Under the World Anti-Doping Code coaches have designated anti-doping roles and responsibilities. Yet, their experiences, opinions and behaviours in relation to these expectations are poorly understood. This study responds directly to this absence of evidence in order to move the field forward. Design: A qualitative thematic analysis approach. Method: Twelve football and rugby league coaches, working in a performance development context, took part in semi-structured interviews to explore their (anti-)doping experiences, opinions and behaviours. Nine coaches participated in follow-up interviews where particular attention was paid to existing anti-doping policy directives. All interviews were analysed using inductive thematic analysis. Results: Coaches were supportive of anti-doping efforts and exerted their influence by monitoring, giving advice and creating the 'right' culture. Performance prioritisation rendered coaches reluctant to engage proactively in addressing anti-doping in their practice; a situation exacerbated by a lack of self-efficacy to advise/act in accordance with the rules. Consequently, coaches tended to rely on others (both internally and externally to their club) to provide anti-doping support, and anti-doping is deemed unnecessary/irrelevant. Critically, coaches' current behaviours were not driven by policy, as they were unaware of expectations and consequences outlined in the Code. Conclusions: Coaches are willing to support anti-doping efforts, but are generally passive in their everyday practice. The gulf between anti-doping policy and coaching practice raises cause for concern for anti-doping policy makers. To bridge this gap systematic programming of activities designed to ensure coaches are able and willing to take a proactive role in doping prevention is required. Highlights: Global anti-doping policy outlines roles and responsibilities for coaches. Yet, our understanding of coaches' doping prevention behaviours is limited. Coaches are supportive of anti-doping, but remain passive for the most part. Findings indicate a gulf between anti-doping policy and coaching practice. Interventions need to be designed to enable coaches to prevent doping in sport.